Experimental Study of a Dual-mode CO2 Heat Pump System with Thermal Storage. (May 2017) - Liu, Fang; Zhu, Weiquan; Cai, Yang
Abstract: This paper presents an experimental study of the performances of a dual-mode CO2 heat pump system with thermal storage. This CO2 system was tested at a variable frequency compressor, variable expansion valve opening as well as variable frequency cooling/heating water pumps. It is found that the performances of CO2 heat pump with thermal storage can be optimized through optimizing thermal stratification of thermal storage tank coupled with heat pump system performances. High compressor frequency benefits the system performances. Expansion valve opening affects the thermal stratification of thermal storage tanks very slightly. The overall COP reaches a maximum when heating and cooling water flow rates were set as 0.1 m 3 /h and 0.2 m 3 /h respectively at compressor frequency of 50 Hz and expansion valve opening of 330 pulses.